A clinical informaticist to support primary care decision making. Issue 4 (1st December 2001) - Swinglehurst, D A; Pierce, M; Fuller, J C A
Abstract : Objectives —To develop and evaluate an information service in which a "clinical informaticist" (a GP with training in evidence-based medicine) provided evidence-based answers to questions posed by GPs and nurse practitioners. Design —Descriptive pilot study with systematic recording of the process involved in searching for and critically appraising literature. Evaluation by questionnaire and semi-structured interview. Setting —General practice. Participants —34 clinicians from two London primary care groups (Fulham and Hammersmith). Main outcome measures —Number and origin of questions; process and time involved in producing summaries; satisfaction with the service. Results —All 100 clinicians in two primary care groups were approached. Thirty four agreed to participate, of whom 22 asked 60 questions over 10 months. Participants were highly satisfied with the summaries they received. For one third of questions the clinicians stated they would change practice in the index patient, and for 55% the participants stated they would change practice in other patients. Answering questions thoroughly was time consuming (median 130 minutes). The median turnaround time was 9 days; 82% of questions were answered within the timeframe specified by the questioner. Without the informaticist, one third of questions would not have been pursued. Conclusion —The clinical informaticist service increased access to evidence for busy clinicians. Satisfaction was high among users and clinicians stated that changes in practice would occur. However, uptake of the service was lower than expected (22% of those offered the service). Further research is needed into how this method of increasing access to evidence compares with other strategies, and whether it results in improved health outcomes for patients.